2016
DOI: 10.1016/j.rppnen.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive repair of Morgagni hernia – A multicenter case series

Abstract: Children may benefit from minimally invasive surgery (MIS) in the correction of Morgagni hernia (MH). The present study aims to evaluate the outcome of MIS through a multicenter study. National institutions that use MIS in the treatment of MH were included. Demographic, clinical and operative data were analyzed. Thirteen patients with MH (6 males) were operated using similar MIS technique (percutaneous stitches) at a mean age of 22.2±18.3 months. Six patients had chromosomopathies (46%), five with Down syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…An italian physician Gian Battista Morgagni firstly described retrosternal CDH through the right sternocostal triangle, in an adult stonecutter, who died for strangulated herniated colon. After this report, this kind of hernia bore his name [14]. As for the age of CMDH diagnosis, there are recent retrospective studies on CMDH, mostly representing adult data and only few series focused on children [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An italian physician Gian Battista Morgagni firstly described retrosternal CDH through the right sternocostal triangle, in an adult stonecutter, who died for strangulated herniated colon. After this report, this kind of hernia bore his name [14]. As for the age of CMDH diagnosis, there are recent retrospective studies on CMDH, mostly representing adult data and only few series focused on children [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, patients with CMDH are asymptomatic, and the pathology is often diagnosed incidentally during a chest X-ray performed for other indications [1]. Rarely patients present symptoms, such as respiratory problems or abdominal pain, and exceptionally the diagnosis is made for a complicated CMDH, usually with an intestinal obstruction [14]. Patients affected by CMDH can present associated malformations: Chromosomal anomalies, mainly Down syndrome, are frequent findings in these patients as well as the presence of other associated congenital malformations such as congenital heart disease, chest wall deformities and intestinal malrotation [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate of Morgagni hernias is not clear, with about 2-15% of recurrent cases after surgery due to remnant sac or absorbable sutures. 13 A search of PubMed using the terms "Morgagni hernia"…”
Section: 김덕기 등 만성적인 소화불량증을 주소로 내원한 고령의 환자에서 우연히 발견된 모르가니 헤르니아mentioning
confidence: 99%
“…The abdominal approach is preferred unless the diagnosis is uncertain. Recurrent rates of 2%-15% postoperatively are reported due to the remnant pouch or otherwise [9]. Only recently has Arevalo, et al reported successful minimally invasive management of Morgagni hernia with robotic use [10].…”
Section: Discussionmentioning
confidence: 99%